Effects of intimate partner violence on the well being of male survivors at Padare in Mutare - Chiriseri, Tamuka (Midlands State University, 2019)
The study sought to find out the effects of intimate partner violence on the wellbeing of male survivors at Padare Men’s forum on Gender, in Mutare. The researcher reviewed relevant literature, theories, as well as previous studies from which the knowledge gap was identified. A qualitative research approach was employed and a phenomological research design was used. The target population comprised of male survivors of intimate-partner violence. Stratified random sampling was used to select 8 male survivors of IPV who were interviewed using in-depth interviews. Data collection procedures included observation of research ethics namely informed consent, confidentiality, anonymity and privacy. A pre-test was conducted with 4 men from Varume Svinurai in Mutare. Demographic data from the interviews was presented using descriptive methods whereas interview data was presented using thematic analysis. Major findings were that a greater percentage of male survivors suffered psychologically, financially and physically due to IPV. Therefore the most common effect of IPV among male survivors were psychological effects followed by physical effects and lastly financial effects. The researcher recommended that information dissemination is required to conscientize the general public on the consequences of violence against men